2007
DOI: 10.1017/s1355770x06003482
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural expansion, forest products as safety nets, and deforestation

Abstract: Incompleteness of insurance markets is a crucial weakness of developing countries.In this context, the poor households of rural regions often exploit common property resources, such as forests, as insurance in case of economics stress. The aim of this paper is to derive the implications of this insurance use on the forest cover, and thus on deforestation. The land-use choice between agricultural land and forest therefore resembles a portfolio diversification. However, I also show that this insurance strategy m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 25 publications
1
34
0
Order By: Relevance
“…Because participation is voluntary, the compared to farming, which provides seasonal and often fluctuating income. Commonly, income from NTFP extraction is less risky compared to farming income, in which case households use NTFP extraction as a risk-free asset to smooth income fluctuations (Delacote, 2007;Alderman and Paxson, 1994). Furthermore, greater integration of NTFP markets relative to agricultural markets in our study areas would mean that income from NTFP extraction and farming are not correlated.…”
Section: Econometric Frameworkmentioning
confidence: 96%
“…Because participation is voluntary, the compared to farming, which provides seasonal and often fluctuating income. Commonly, income from NTFP extraction is less risky compared to farming income, in which case households use NTFP extraction as a risk-free asset to smooth income fluctuations (Delacote, 2007;Alderman and Paxson, 1994). Furthermore, greater integration of NTFP markets relative to agricultural markets in our study areas would mean that income from NTFP extraction and farming are not correlated.…”
Section: Econometric Frameworkmentioning
confidence: 96%
“…Similarly, Delacote (2007) showed that when tree production is seen as having relatively low profitability and low risk compared to agricultural production, risk-averse households will plant trees to smooth consumption. However, if risk in agriculture is reduced, forest cover will be reduced because the need for consumption smoothing provided by the trees is less.…”
Section: Theorymentioning
confidence: 99%
“…Ward et al (2010) reports that gender balance in agricultural productivity brings about equal distribution of resources resulting in production efficiency and increased incomes. Gender complementarity is necessary for commercialization of underutilized plants since each of the actors have a unique role to play (De Caluwe 2011, Delacote 2007). …”
Section: Luffa Sponge Value Chains In Ugandamentioning
confidence: 99%